#### Answer

$(f+g)(x)=6x-7$
$(f+g)(5)=23$

#### Work Step by Step

$(f+g)(x)=f(x)+g(x)$
$=4x+2+2x-9$
$=6x-7$
Plugin $x=5$ into $6x-7.$
$(f+g)(5)=6\times5-7=30-7=23$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$(f+g)(x)=6x-7$
$(f+g)(5)=23$

$(f+g)(x)=f(x)+g(x)$
$=4x+2+2x-9$
$=6x-7$
Plugin $x=5$ into $6x-7.$
$(f+g)(5)=6\times5-7=30-7=23$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.